AKSI SOSIAL PEDULI LINGKUNGAN SEHAT, INDAH DAN BERSIH UNTUK ANAK-ANAK - Wagisri, Wagisri; Apriani, Anggun; Halimatusakdiyah, Halimatusakdiyah; Fatma, Napisah Dwi; Safitri, Sari (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2023)
The aim of community service activities is to provide education to the community regarding the importance of a healthy, beautiful and clean environment. Environmental cleanliness is the main key in maintaining health. The implementing method for this activity uses socialization and social action. The activity is carried out for one week starting from observation, licensing, implementation, closing the activity, and making a report. The results of service activities provide a positive influence on the surrounding community, namely having an awareness of protecting the environment and implementing a clean and healthy lifestyle. Furthermore, a clean environment and good sanitation will help prevent the spread of infectious diseases and create a safe and comfortable environment for children.